(untitled) (Proceeding of the International Conference on Arts and Humanities, 2018)
This research on the color scheme of Mural Paintings and Decorations in Interior Architecture. (Case Study: Temples in Khonkaen) This research shows the decorations and the color schemes in some important temples in Khonkaen which have significant mural paintings. The temples are Wat Sa Bua keo , Wat Sanuan Wari Phatthanaram, Wat Matchim Wittayaram. The conclusions of the color scheme of Mural Paintings of 3 temples in Khonkaen are :Wat Sa Bua keo the color and style of the Mural Painting inside and outside are the same. Persumably they used the same painters working at the same time.The background is light color (cream color) and the story is painted in bright color. Wat Sanuan Wari Phatthanaram the color and style of the Mural Painting inside and outside are the same.The background is light color (cream color) and the story is painted in bright color, thus making the painting look airy. The painting inside is on the wall over the windows, because the temples is small and the windows are wide, so there is no space for painting between the windows like in the other temples. Wat Matchim Wittayaram, there are paintings inside and outside. The painting inside is only on the wall behind the Buddha image. There is no painting on the other wall. The color inside and outside are different, Perhaps the painters were different groups working at different times. The color outside has blue tone on the background instead of cream tone like in the other temples. In this research, the researcher uses Pantone Color chart to match the colors at the site and uses YMCK mode to mix colors in computer. If the color is not exactly reproduced correct because of the printing process, interested persons can reproduce the colors by using the code given in this research to obtain the closest actual colors of this study.